The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1177/00220345900690031101
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis in Odontoclasts and Osteoclasts Using Microperoxidase as a Tracer

Abstract: Microperoxidase (MP, a peptide tracer) was intravenously injected into rats after six days of tooth movement by the Waldo method. Bone resorption was seen along the distal bone surface of the inter-radicular septum of the upper first molar, and tooth root resorption occurred along the mesial and distal surfaces of the distal root of the same molar. Odontoclasts were smaller in size and numbers than osteoclasts, but had the same organelles [multiple nuclei, ruffled borders (RB), clear zones, vacuoles, mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…The presence of cementoblast-like or fibroblast-like stromal cells in association with odontoclasts has been reported in root resorption of deciduous teeth (Sasaki et al, 1990a,b;Tanaka et al, 1990;Sahara, 1998). Similarity of the tooth resorption-repair sequence (i.e., root resorption and cementum formation) to the bone remodeling sequence has also been pointed out (Sasaki et al, 1990a,b;Sahara, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…The presence of cementoblast-like or fibroblast-like stromal cells in association with odontoclasts has been reported in root resorption of deciduous teeth (Sasaki et al, 1990a,b;Tanaka et al, 1990;Sahara, 1998). Similarity of the tooth resorption-repair sequence (i.e., root resorption and cementum formation) to the bone remodeling sequence has also been pointed out (Sasaki et al, 1990a,b;Sahara, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, some authors considered that these mononuclear cells might scavenge the bone surface at the end of osteoclastic resorption (Heersche, 1978; Tran Van et al, 1982;Everts et al, 2002) and that the cement line/reversal line seen on the resorbed surface might be formed by these mononuclear cells (Heersche, 1978; Tran Van et al, 1982;McKee and Nanci, 1996a;Everts et al, 2002). In the case of tooth resorption, it was also reported that similar kinds of mononuclear cell types, e.g., cementoblast-like cells (Sasaki et al, 1990), machrophage-like cells or fibroblast-like cells (Tanaka et al, 1990;Okamura et al, 1993), and a special class of mononuclear cells (Bosshardt and Schroeder, 1998) were seen lining the resorption surface. In the present study, we also found that numerous mononuclear cells was seen to populate the resorbed enamel surface after the withdrawal of the odontoclasts and prior to the onset of repair cementum-like tissue formation.…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that osteoclasts undergoing even more differentiation have a greater number of nuclei with a higher bone resorption activity (Teti et al, 1991;Lees et al, 2001;Manolson et al, 2003). Since odontoclasts normally have fewer nuclei and less clear zones compared with osteoclasts (Tanaka et al, 1990;Ne et al, 1999), we hypothesized that odontoclasts possess less cell differentiation in their matrix resorption characteristics than osteoclasts. This may be a fundamental difference that explains why the dental root is less susceptible to resorption by multinucleated cells as compared with alveolar bone.…”
Section: Introductionmentioning
confidence: 93%